Chemistry and engineering of cyclodextrins for molecular imaging. (20th September 2017) - Lai, Wing-Fu; Rogach, Andrey L.; Wong, Wing-Tak
Abstract : Cyclodextrins (CDs) are naturally occurring cyclic oligosaccharides that show favourable properties for probe design and development. Abstract : Cyclodextrins (CDs) are naturally occurring cyclic oligosaccharides bearing a basket-shaped topology with an "inner–outer" amphiphilic character. The abundance of hydroxyl groups enables CDs to be functionalized with multiple targeting ligands and imaging elements. The imaging time, and the payload of different imaging elements, can be tuned by taking advantage of the commercial availability of CDs with different sizes of the cavity. This review aims to offer an outlook of the chemistry and engineering of CDs for the development of molecular probes. Complexation thermodynamics of CDs, and the corresponding implications for probe design, are also presented with examples demonstrating the structural and physiochemical roles played by CDs in the full ambit of molecular imaging. We hope that this review not only offers a synopsis of the current development of CD-based molecular probes, but can also facilitate translation of the incremental advancements from the laboratory to real biomedical applications by illuminating opportunities and challenges for future research.